Exploring Religiosity among the Educated Generation of the 70s in Yazd City: A Qualitative Study - Ahmad Kalateh Sadati; Asal Razavi (Strategic Research on Social Problems)
Introduction Religion continues to be a vital human institution, adapting and thriving despite significant changes in its social roles. Contrary to classical sociological predictions of religious decline, the latter half of the 20th century saw a resurgence of faith, especially in Western Europe and America. For example, Protestantism in the United States has experienced considerable growth, with a multitude of denominations emerging. Projections indicate that by 2025, Christianity and Islam will have approximately 2.7 billion and 1.97 billion adherents, respectively, with Islam recognized as the fastest-growing religion worldwide, boasting a growth rate of 1.84% from 2000 to 2013. While institutional religion may be diminishing in Western societies, personal and private expressions of spirituality are on the rise. Research suggests that perceived hypocrisy within religious communities can lead to disbelief and apostasy. However, theories of secularization have not fully captured the complexities of this transformation. In contrast, Islam is experiencing growth in many societies although the nature of this expansion remains largely unexplored. In Iran, generational shifts in religious beliefs and practices—shaped by globalization and modernity—have created a notable divergence between the values of youth and those of their parents. This study aimed to examine the religious experiences and interpretations of young people from religious families, particularly within the context of Yazd.